-9-9-5f=-8f+9

Simple and best practice solution for -9-9-5f=-8f+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9-9-5f=-8f+9 equation:



-9-9-5f=-8f+9
We move all terms to the left:
-9-9-5f-(-8f+9)=0
We add all the numbers together, and all the variables
-5f-(-8f+9)-18=0
We get rid of parentheses
-5f+8f-9-18=0
We add all the numbers together, and all the variables
3f-27=0
We move all terms containing f to the left, all other terms to the right
3f=27
f=27/3
f=9

See similar equations:

| -2x-(1/2)=1/4 | | -180=-8k-5(4K+8) | | 2(z-8)=2 | | -7(-3-x)=-2(2-x) | | -6(b+3)+6b=6b=-6(-4b+3) | | k/8=0.8k= | | 6(4+5a)+10a=-10(1-6a)-6 | | 3(–4z+6)=–(12−6z) | | 18-3t=-12 | | -20k-13k+-11=10 | | 8(x+9)=72-5x | | 2k+18=0 | | 12(n)=5n-6 | | -10b-3+3b=4-6b | | 18=14.5m=6m+12 | | 6n3=15 | | 121/2=2w+2(31/2) | | -6+n=-3 | | p-9=-5(p-3) | | .15-3x=-6 | | 7(x+2)-1=3x+4(3+x) | | -8x-7=-3x-17 | | 6x+5-9x=-40 | | 7x=7(7)=0 | | (2x²-3x+1)=+(4x-7) | | 0.66666667n-5=-2 | | 14=2(r-9) | | –10b−3+3b=4−6b | | 10m-19=3m+2 | | 4u+5=37 | | -7(4x+7)=3+4(-4-6) | | 15(x+14)=60 |

Equations solver categories